Dual Positive Regulation of Embryo Implantation by Endocrine and Immune Systems – Step‐by‐Step Maternal Recognition of the Developing Embryo. (12th January 2016) - Fujiwara, Hiroshi; Araki, Yoshihiko; Imakawa, Kazuhiko; Saito, Shigeru; Daikoku, Takiko; Shigeta, Minoru; Kanzaki, Hideharu; Mori, Takahide
Abstract : In humans, HCG secreted from the implanting embryo stimulates progesterone production of the corpus luteum to maintain embryo implantation. Along with this endocrine system, current evidence suggests that the maternal immune system positively contributes to the embryo implantation. In mice, immune cells that have been sensitized with seminal fluid and then the developing embryo induce endometrial differentiation and promote embryo implantation. After hatching, HCG activates regulatory T and B cells through LH/HCG receptors and then stimulates uterine NK cells and monocytes through sugar chain receptors, to promote and maintain pregnancy. In accordance with the above, the intrauterine administration of HCG‐treated PBMC was demonstrated to improve implantation rates in women with repeated implantation failures. These findings suggest that the maternal immune system undergoes functional changes by recognizing the developing embryos in a stepwise manner even from a pre‐fertilization stage and facilitates embryo implantation in cooperation with the endocrine system.